How transboundary processes connect commons in Japan and Thailand: A relational analysis of global commodity chains and East Asian economic integration. (11th February 2020) - Middleton, Carl; Ito, Takeshi
Abstract : In this paper, with a focus on Japan and Thailand, we outline a relational environmental and economic history of East Asian economic integration (EAEI) and its implication for the commons in both places. We draw attention in particular to global commodity chains as relational processes not only of trade and investment, but also geopolitics and aid, to argue that these transborder processes have connected together commons in distant localities resulting in their simultaneous enclosure, dispossession and (re‐)commoning with implications for community vulnerabilities in positive and negative ways. To demonstrate this argument we analyse three periods of EAEI: the late nineteenth century until World War II, when Japan and Thailand both began to modernise and new trade and geopolitical relations emerged in the context of colonialism; the post‐World War II recovery until the Plaza Accord in 1986, during which time Japan rapidly industrialised, as did Thailand to a lesser extent and regionalism was largely defined by US hegemony; and the post‐Plaza Accord period, when Japan deindustrialised its labour intensive manufacture and heavy industry and Thailand rapidly industrialised and EAEI became defined by new and intensified global commodity chains.